ppENK Gene Methylation Status in the Development of Pancreatic Carcinoma - Lixin Yang; Hong Yang; Jingnan Li; Jianyu Hao; Jiaming Qian (Gastroenterology Research and Practice)
Objective. To explore the association of hypermethylation of the proenkephalin gene (ppENK) with pancreatic carcinoma and to identify the effects of a demethylating agent on pancreatic cell lines. Method. Human pancreatic cancer tissues and five pancreatic carcinoma cell lines, as well as normal pancreatic tissue, were used. ppENK methylation status was detected by MS-PCR (methylation-specific PCR). Results. Methylation of ppENK was detected in 90.3% (28/31) of the human pancreatic carcinoma tissues but was not seen in normal pancreatic tissue. There was no correlation between the extent of methylation of ppENK and the clinicopathological features of the pancreatic carcinomas. Methylated ppENK was detected in all the pancreatic cancer cell lines and was associated with loss of mRNA expression in the pancreatic carcinoma cell lines and normal pancreatic tissue. After treatment with 5-aza-dC, methylated ppENK was not detected and the inhibition of ppENK mRNA expression was reversed. Conclusions. Inhibition of ppENK expression by a change in its methylation status plays an important role in pancreatic carcinogenesis. ppENK methylation is thus an important molecular event that distinguishes pancreatic carcinoma tissue from normal pancreatic tissue. Effects on cell growth, apoptosis, and the cell cycle may contribute to changes of ppENK methylation status.